Hermansky-Pudlak Syndrome and Chediak-Higashi Syndrome: Disorders of Vesicle Formation and Trafficking - Huizing, Marjan; Anikster, Yair; Gahl, William A. (Thrombosis and Haemostasis, 2001)
The rare autosomal recessive metabolic disorders Hermanky-Pudlak syndrome (HPS) and Chediak-Higashi syndrome (CHS) share the clinical findings of oculocutaneous albinism and a platelet storage pool deficiency. In addition, HPS exhibits ceroid lipofuscinosis and CHS is characterized by infections and an accelerated phase. The two disorders result from defects in vesicles of lysosomal lineage. Of the two known HPS-causing genes, HPS1 has no recognizable function, while ADTB3A codes for a subunit of an adaptor complex responsible for new vesicle formation from the trans-Golgi network. Other HPS-causing genes are likely to exist. The only known CHS-causing gene, LYST, codes for a large protein of unknown function. In general, HPS appears to be a disorder of vesicle formation and CHS a defect in vesicle trafficking. These diseases and their variants mirror a group of mouse hypopigmentation mutants. The gene products involved will reveal how the melanosome, platelet dense body, and lysosome are formed and trafficked within cells.
Keywords: Albinism; platelet dense bodies; giant lysosomes; LYST; intracellular trafficking